A dimensão subjetiva das relações de trabalho na economia solidária - Lima, Maria das Graças de (2011)
The current research substantiated by the Socio-Historical Psychology sought to capture the subjective dimension of work relations from the current experiences of solidarity economy in the urban context of the Metropolitan Region of São Paulo. We tried to identify the extent to which elements of the subjective dimension (senses and meanings, needs and motives) boost and strengthen or undermine and withhold the development and consolidation of the Economic Solidarity Enterprises (SEEs). This Research in Socio-Historical perspective considers the individual and society, subjectivity and objectivity without dichotomies, such as parts of a whole, which interact dialectically constituting and being constituted both procedurally, in constant motion processing. Consistent with this approach this research is characterized as a qualitative research is the methodology to investigate and analyze the human and social phenomena in its dynamic process. The procedures and instruments for data collection sought to contextualize the social, economic, historical and cultural realities of the respondents surveyed and the ESS as well as enabling an analysis of subjective aspects through the free expression of the research participants, in which the main instrument used were open individual or collective interviews according to the availability of research subjects. The term "Subjective Dimension of Reality," coined by Furtado (2002) seeks to explicit that reality is constituted by the set of social and historical realities in its objective basis (economic and physical) and subjective bases (production values), from the dialectic established between subjectivity and objectivity. The subjective dimension of reality takes shape as a synthesis between the objective conditions and reveals how the subjects interpret the reality to which they are and this way of interpreting reality is also constitutive of reality and is inscribed in culture field. The data analysis confirmed the initial hypothesis that the elements that constitute the subjective dimension of reality can both stimulate and strenght as well as undermine and delay the development and consolidation of the ESS